User Expectations and the Willingness to Adopt Electronic Medical Records in Primary Healthcare - Rahman, Ferry Fadzlul (GLOBAL HEALTH SCIENCE GROUP, 2024)
In the contemporary landscape of primary healthcare, the transition from paper-based systems to electronic medical records (EMRs) is a pivotal advancement aimed at enhancing efficiency and patient care. This study focuses on the intricate relationship between user expectations and the willingness of healthcare professionals to adopt EMRs. By exploring user perceptions, anticipated benefits, and potential challenges, the research aims to provide valuable insights into the dynamics shaping the successful implementation of EMRs in primary healthcare settings. The objective of the study was to investigate the correlation between user expectations and the willingness to utilize electronic medical records at Sidomulyo Primary Healthcare Center in Samarinda City. This research employed an observational analytic approach with a cross-sectional design, conducted in April 2023data was collected using the sampling technique involving stratified random sampling, resulting in a sample size of 48 healthcare professionals at Sidomulyo Primary Healthcare Center in Samarinda City. Inclusion criteria are determined by selecting health workers who have been trained to fill out electronic medical records. Statistical analysis utilized the Chi-Square test to examine the relationship between variables. The research findings revealed a p-value of <0.001 (p < 0.05), indicating a significant correlation between user expectations and the willingness to adopt electronic medical records at Sidomulyo Primary Healthcare Center in Samarinda City. This research is implies the importance of addressing user needs and expectations for a successful implementation. Tailoring strategies to enhance user satisfaction and communication about the benefits can contribute to a smoother adoption process in healthcare settings.